Effects of gamma radiation on the phenolic compounds and in vitro antioxidant activity of apple pomace flour during storage using multivariate statistical techniques - Ito, Vivian Cristina; Alberti, Aline; Avila, Suelen; Spoto, Marta [UNESP]; Nogueira, Alessandro; Wosiacki, Gilvan (Elsevier B.V., 2016)
The aim of this study was to evaluate the effects of gamma radiation on the phenolic compounds and antioxidant activity of apple pomace flour (0,1 and 2 kGy dose at times of 0,3, 6 and 9 months) during storage using multivariate techniques. The a* and h degrees colour attributes at a dose of 1 kGy, and the phenolic compound phloridzin showed constant levels during the experiment. The dose of 1 kGy at time 0 provides better results for antioxidant activity, total phenolic compounds and some individual compounds. Chlorogenic acid and its class of hydroxycinnamic acids increased proportionally with time in the irradiated samples. The chemometric approach made it possible to observe the influence of irradiation and storage time on the samples of apple pomace flour. The effect of irradiation on the phenolic compounds was related to the intensity and the characteristics of each individual compound. Industrial relevance: Irradiation has been shown to be an economically viable alternative for the treatment of foods; it has several advantages compared to traditional processing methods and can be applied independently or combined with existing techniques such as dehydration. Thus, this combination of treatments, as well as increasing the shelf life of apple pomace also increases the concentrations of nutrients and can be applied in the pharmaceutical, cosmetics and food industries. This advantage can translate into economic advantages, with added values in various applications and help to partially reduce negative impacts on the environment. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Phytochemicals; Irradiation; Stability; Multivariate statistical techniques